Influence of zwitterionic SAMs on protein adsorption and the attachment of algal cells - Bauer, Stella; Alles, Maria; Finlay, John A.; Callow, James A.; Callow, Maureen E.; Rosenhahn, Axel (Journal of biomaterials science. Polymer edition, 2014)
Zwitterionic polymers are non-fouling materials with immense potential for a range of biological applications. Here, we describe the resistance of zwitterionic self-assembled monolayers prepared from different solution ratios of positively and negatively charged thiols towards the adhesion of proteins, zoospores of the green alga Ulva linza, and cells of the unicellular alga Navicula perminuta. While mixed zwitterionic surfaces with a high hydrophilic nature significantly reduced the adhesion strength of the two algae, the positively and negatively charged components were far less effective.
Gesehen am 16.10.2020